2016
DOI: 10.1515/rebs-2016-0031
|View full text |Cite
|
Sign up to set email alerts
|

Returning to General and Vocational High-Schools in Indonesia

Abstract: Promoting vocational secondary education can be an appealing option for developing countries in order to improve labour market outcomes. The main reason for the promotion of vocational education is the increase of the labour force. The debate regarding the benefit resulted from vocational education, as opposed to general education is far from conclusive. This paper analyses the return to schooling of vocational and general highschools in Indonesia using Indonesian Family Life Survey (IFLS). The study finds no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 19 publications
1
11
1
Order By: Relevance
“…On the other hand, studies in Tanzania (Kahyarara & Teal 2008) and Suriname (Horowitz & Schenzler 1999) found that students from general schools have higher incomes than those from professional ones, while in Germany (Lechner 2000), South Korea (Chae & Chung 2009), Romania (Malamud & Pop-Eleches 2008) and Indonesia (Bellei 2009, Mahirda & Wahyuni 2016 the results between schools did not differ significantly.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…On the other hand, studies in Tanzania (Kahyarara & Teal 2008) and Suriname (Horowitz & Schenzler 1999) found that students from general schools have higher incomes than those from professional ones, while in Germany (Lechner 2000), South Korea (Chae & Chung 2009), Romania (Malamud & Pop-Eleches 2008) and Indonesia (Bellei 2009, Mahirda & Wahyuni 2016 the results between schools did not differ significantly.…”
Section: Introductionmentioning
confidence: 90%
“…Vocational education may be an option for developing countries seeking to improve youngsters' opportunities and earnings in the labor market, by preparing them with specific job skills and trainings. However, the debate about the benefits of this type of school is inconclusive in the international literature (Mahirda & Wahyuni 2016). In some countries, vocational students get higher incomes when compared to general school students.…”
Section: Introductionmentioning
confidence: 99%
“…This encouraged the Ministry of Education and Culture of the Republic of Indonesia to design a policy to increase the number of Vocational Schools by targeting an improved ratio of Vocational Schools vs. General Schools, from 50:50 in 2010 to 70:30 in 2015. To achieve this goal, the constructions of the general schools' buildings were suspended, tools and infrastructures for technical schools were prioritized, and some general schools would be modified to become vocational schools (Mahirda & Wahyuni, 2016;Newhouse & Suryadarma, 2011). Buabeng-Andoh (2019) states that learning mathematics and science, as well as reading courses in Vocational High Schools (VHSs) can escalate vocational school graduates' opportunities in getting the desired jobs and providing more chances for them to pursue higher education.…”
Section: Introductionmentioning
confidence: 99%
“…Vocational education has the output of preparing students to work after graduation [4]. The output can be categorized as an entrepreneur or working in a company.…”
Section: Introductionmentioning
confidence: 99%